2021
DOI: 10.1111/ajt.16431
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient COVID-19 outcomes in solid organ transplant recipients compared to non-solid organ transplant patients: A retrospective cohort

Abstract: Immunosuppression and comorbidities might place solid organ transplant (SOT) recipients at higher risk from COVID‐19, as suggested by recent case series. We compared 45 SOT vs. 2427 non‐SOT patients who were admitted with COVID‐19 to our health‐care system (March 1, 2020 ‐ August 21, 2020), evaluating hospital length‐of‐stay and inpatient mortality using competing‐risks regression. We compared trajectories of WHO COVID‐19 severity scale using mixed‐effects ordinal logistic regression, adjusting for severity sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
93
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 23 publications
4
93
2
6
Order By: Relevance
“…Mortality rates reported among SOT recipients with COVID-19 vary widely from 3% to over 30% depending on organ type, comorbid conditions, geographical location, COVID-19 treatment, and time of report during the pandemic [1,2]. Data are conflicting as to whether SOT recipients have higher risk of mortality compared with non-SOT recipients [2][3][4][5][6][7][8]. Furthermore, SOT recipients often have comorbidities, such as diabetes, chronic kidney disease, and cardiac disease, that have been associated with more severe cases of COVID-19 and an increased risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates reported among SOT recipients with COVID-19 vary widely from 3% to over 30% depending on organ type, comorbid conditions, geographical location, COVID-19 treatment, and time of report during the pandemic [1,2]. Data are conflicting as to whether SOT recipients have higher risk of mortality compared with non-SOT recipients [2][3][4][5][6][7][8]. Furthermore, SOT recipients often have comorbidities, such as diabetes, chronic kidney disease, and cardiac disease, that have been associated with more severe cases of COVID-19 and an increased risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of pregnant women with heart disease were too small for the risk in this group to be estimated. Other studies of outcome of COVID-19 in solid organ transplant recipients and other individuals using immunosuppressants have been based only on patients admitted to hospital [11,12]. Such studies cannot assess the risks to immunosuppressed individuals in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that despite higher risk profile, solid organ transplant recipients improved rapidly and their disease severity declined at a faster rate than others. 11 The pathogenesis of COVID-19 is thought to comprise an interplay between direct virus induced injury and the host response, with evidence suggesting that a dysregulated and hyperintense immune response mediates more severe disease. 12 As we know that immunosuppressive agents modulate different aspects of the host immune response, the severity of COVID-19 disease could potentially be affected by the type, combinations, and dosages of immunosuppression being used.…”
Section: Discussionmentioning
confidence: 99%